2005
DOI: 10.1248/jhs.51.207
|View full text |Cite
|
Sign up to set email alerts
|

Sex Difference in the Influence of Dietary Protein Deficiency on the Fate of Methylmercury in Mice and Rats

Abstract: We investigated sex difference in the influence of dietary protein deficiency on the fate of methylmercury (MeHg) using both sexes of C57BL/6N mice and Wistar rats to determine the universality of the influence. One day after oral administration of MeHg (20 mol/kg), regardless of sex and species, urinary Hg excretion was suppressed by dietary protein deficiency, whereas fecal excretion was not affected. At that time, tissue Hg concentrations in both sexes of the specified species were similarly influenced by d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…It has been demonstrated that the fate of MeHg is affected by dietary levels of protein and sulfur amino acids, [28][29][30][31][32][33] through the alterations in the metabolism of thiol compounds such as GSH 28,29,34,35) and in the amino acid transport. 29,31,32,34) Interestingly, a dietary Met supplement to the refined diet increased Hg accumulation in the liver and decreased that in the kidney regardless of dietary protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the fate of MeHg is affected by dietary levels of protein and sulfur amino acids, [28][29][30][31][32][33] through the alterations in the metabolism of thiol compounds such as GSH 28,29,34,35) and in the amino acid transport. 29,31,32,34) Interestingly, a dietary Met supplement to the refined diet increased Hg accumulation in the liver and decreased that in the kidney regardless of dietary protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,10,31) In addition, the percentage of Hg accumulated in the brain to Hg administered was also higher in LPD-fed mice due to similar body and brain weights. 31) However, no difference was observed in the brain Hg concentration between the dietary groups in rats (Fig. 1).…”
Section: Discussionmentioning
confidence: 91%
“…4D) by dietary protein deficiency. The decrease in urinary Hg excretion by the lowered dietary protein level is also observed in not only male mice 6,7,10) but also in female animals 31) despite the marked sex difference in the fate of MeHg in intact animals, 3,4) suggesting that this decrease would be universally caused by dietary protein deficiency. It has been suggested that urinary excretion of MeHg is regulated by many processes according to the following mechanism.…”
Section: Discussionmentioning
confidence: 93%
“…We recently revealed that, regardless of the marked sex difference in the fate of MeHg in intact C57BL mice, [11][12][13] its fate was similarly affected by a dietary modification (dietary protein deficiency) regardless of sex, except for the gonads. 14) We, therefore, suggested that some factors that affect the fate of MeHg might be similarly influenced by this dietary modification both in males and females.…”
Section: Fig 1 Time-dependent Changes In Tissue and Excreted Hg In mentioning
confidence: 88%